1997
DOI: 10.1085/jgp.109.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Barbiturate Inhibition of Acetylcholine Receptor Channels

Abstract: We used patch clamp techniques to study the inhibitory effects of pentobarbital and barbital on nicotinic acetylcholine receptor channels from BC3H-1 cells. Single channel recording from outside-out patches reveals that both drugs cause acetylcholine-activated channel events to occur in bursts. The mean duration of gaps within bursts is 2 ms for 0.1 mM pentobarbital and 0.05 ms for 1 mM barbital. In addition, 1 mM barbital reduces the apparent single channel current by 15%. Both barbiturates decrease the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…The [Cu 2ϩ ] cis -induced changes in these parameters were fitted with two or three exponentials. These findings are in agreement with those fits where drugs typically induce open channel block (18).…”
Section: Effects On A␤(1-42) Channel Kinetics Within the Burstsupporting
confidence: 92%
See 1 more Smart Citation
“…The [Cu 2ϩ ] cis -induced changes in these parameters were fitted with two or three exponentials. These findings are in agreement with those fits where drugs typically induce open channel block (18).…”
Section: Effects On A␤(1-42) Channel Kinetics Within the Burstsupporting
confidence: 92%
“…The Cu 2ϩ -induced changes in the kinetics of the bursts and the events within the burst are described at least by two exponentials. This behavior appears to be in agreement with that of open channel blocking drugs, which exhibit a two-phase change in current kinetics (18), suggesting that Cu 2ϩ may act on both open and closed states of the channel. Cu 2ϩ also affects desensitization of the A␤(1-42) channels (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings can be explained by the fact that the blocked receptor may close, with or without trapping the blocker molecule in its site (37,38). Another alternative explanation could be related to the presence of two or more sequential blocking sites in the pore (39,40). In agreement with this, studies of the action of the anthelmintic morantel at the muscle AChR from Ascaris have suggested a complex channel blockade mechanism that could be explained by the presence of two blocking sites within the channel pore (41).…”
Section: Achrs By Levamisolementioning
confidence: 68%
“…By contrast, photolabeling at M2-9 was either not inhibited or potentiated, which indicates that [ 3 H]R-mTFD-MPAB can bind in the ion channel near M2-9 and M2-13 when pentobarbital binds at the level of M2-2 and M2-6. Analysis of the inhibition of mouse muscle nAChR by pentobarbital and barbital indicated that they do not compete for a single site but that the binding of one destabilized the other (Dilger et al, 1997). Our results provide the first evidence that two barbiturates can bind simultaneously and in close proximity in the ion channel.…”
mentioning
confidence: 64%
“…Barbiturates act as positive allosteric modulators of GABA A Rs (MacDonald and Olsen, 1994;Löscher and Rogawski, 2012), the in vivo target for many of the anesthetic actions of pentobarbital (Zeller et al, 2007). On the other hand, barbiturates act as noncompetitive/ allosteric inhibitors of muscle-type nAChRs, as shown using electrophysiological (Gage and McKinnon, 1985;Dilger et al, 1997;Krampfl et al, 2000) and ion flux assays (de Armendi et al, 1993).…”
Section: Introductionmentioning
confidence: 99%